Report of the 2nd Arctic Science Ministerial: Co-operation in Arctic Science – Challenges and Joint Actions (2018)
The rapid changes happening in the Arctic are impacting the fragile Arctic ecosystem and have deep impacts on the people living there. Arctic changes are also impacting the global system such as influencing the climate system or sea levels changes. There is a sense of urgency among decision-makers and awareness in the public opinion regarding the global importance of changes taking place in the Arctic. These challenges demand for coordinated and carefully planned collective efforts, as no country can work in isolation in this difficult environment, under harsh working conditions.